Respuesta :

Answer:

Step-by-step explanation:

a). [tex]\frac{5\pm\sqrt{-4}}{3}[/tex] = [tex]\frac{5}{3}\pm \frac{\sqrt{-4}}{3}[/tex]

               = [tex]\frac{5}{3}\pm\frac{2\sqrt{(-1)} }{3}[/tex]

               = [tex]\frac{5}{3}\pm\frac{2i}{3}[/tex] [Since, i = [tex]\sqrt{(-1)}[/tex]]

b). [tex]\frac{10\pm\sqrt{-16}}{2}[/tex] = [tex]\frac{10}{2}\pm \frac{\sqrt{-16}}{2}[/tex]

                  = [tex]5\pm \frac{4\sqrt{-1}}{2}[/tex]

                  = 5 ± 2i [Since, i = [tex]\sqrt{(-1)}[/tex]]

c). [tex]\frac{-3\pm \sqrt{-144}}{6}[/tex] = [tex]-\frac{3}{6}\pm \frac{\sqrt{-144}}{6}[/tex]

                    = [tex]-\frac{3}{6}\pm \frac{12\sqrt{-1}}{6}[/tex]

                    = [tex]-\frac{1}{2}\pm 2\sqrt{-1}[/tex]

                    = [tex]-\frac{1}{2}\pm 2i[/tex] [Since, i = [tex]\sqrt{(-1)}[/tex]]

ACCESS MORE